Social protection in Ghana and Kenya through an inclusive development Lens. Complex effects and risks. (March 2020) - Pouw, Nicky R.M.; Rohregger, Barbara; Schüring, Esther; Alatinga, Kennedy A.; Kinuthia, Bethuel; Bender, Katja
Highlights: Social protection impacts on material, relational and subjective wellbeing. Inclusive growth effects are only generated by the not-so-poor, who have assets and labour. Spill-over effects on social capital and perceptions of self-reliance and citizenship can be positive or negative. Transaction costs of accessing social protection are often too high for the poorest and most marginalized. Power inequities and clientelism aggrevate programme design and implementation failure. Abstract: Social protection research in African economies is growing along with global and national policy debates on inclusive growth and development. Yet, empirical evidence on the nature and scope of the effects, in particular on the poorest and most vulnerable, is scant. This article makes both a theoretical and empirical contribution by analyzing the complex effects and risks of social protection policies in Ghana and Kenya. It proposes a comprehensive inclusive development framework for analyzing social protection impacts. Based on a two-years study on the multidimensional wellbeing effects in rural communities in both countries, it is found that social protection impacts food, education, health and to a limited extent productivity levels of individuals and households, their family and community relations and social equity, as well as perceptions of self-reliance and citizenship. Risks involve exclusionary social-economic and political mechanisms and power inequities aggrevate programme design and implementation failures that exclude the poorest from accessing social protection at multi-scalar levels in the first place.